Safety, tolerability, and immunogenicity of INO-4500, a synthetic DNA-based vaccine against Lassa virus, in a phase 1b clinical trial in healthy Ghanaian adults - Koram, Kwadwo Ansah; Walker, Kathleen A.; Orizu, Bonaventure; Marrero, Idania; Boyer, Jean; Yang, ShuPing; Broderick, Kate E.; Kusi, Kwadwo Asamoah; Kyei-Baafour, Eric; Ofori, Ebenezer Addo; Pobee, Abigail; Adu-Amankwah, Susan; et al. (Frontiers in Immunology, 2025)
BackgroundLassa fever (LF) is an acute viral hemorrhagic illness endemic to West Africa, with no licensed vaccines or targeted treatments available, highlighting a critical gap in global health preparedness. T cell-mediated immunity plays a central role in viral control and survival. Synthetic DNA vaccines offer a promising strategy to induce both humoral and cellular immunity against LF.MethodsA Phase 1b, randomized, double-blind, placebo-controlled trial was conducted to assess the safety, tolerability, and immunogenicity of INO-4500, a DNA vaccine encoding the Lassa virus (Josiah strain) glycoprotein precursor (GPC). A total of 220 healthy adults were randomized to receive either 1 mg or 2 mg of INO-4500 (intervention), or placebo, administered intradermally (ID) followed by electroporation (EP) at Day 0 and Week 4. Safety was evaluated through Week 48. Primary immunogenicity endpoints included humoral and cellular immune responses at multiple timepoints post-vaccination.ResultsINO-4500 was well tolerated, with no Grade 3 or higher treatment-emergent adverse events (TEAEs) deemed to be related to the intervention; 88.6% of all TEAEs were Grade 1. No cases of attributable hearing loss were reported. INO-4500 groups demonstrated statistically significant increases in Lassa virus GPC-specific binding antibodies at Weeks 6 and 12 compared to placebo, with the 2 mg group eliciting the strongest responses. T cell responses remained elevated above baseline through Week 48 in both INO-4500 groups, indicating durable cellular immunity.ConclusionsDNA vaccine INO-4500 was well tolerated and elicited durable humoral and cellular immune responses in healthy adults. These findings support further clinical development of INO-4500 as a potential preventive vaccine to reduce LF-associated morbidity and mortality in endemic regions.Clinical Trial Registrationhttps://clinicaltrials.gov, identifier NCT04093076